x (x-3) = 0
x = 0 or x = 3
before looking at your answer i found the answer to be 0 too but like this:
was my way right
No, because -0x-0x is not -3x
You missed the x = 3 root entirely.
Please do it my way :)
If you insist on completing the square:
x^2 - 3x = 0
(-3/2)^2 = 9/4
x^2 - 3 x + 9/4 = 9/4
(x-3/2)^2 = 9/4 =3/2
x- 3/2 = +/- 3/2
x = 3/2 + 3/2 = 3
x = 3/2 - 3/2 = 0
by the way
x = 5
x+2 = 0
x = -2
do i always have to mention the ors
If it is a quadratic, in general it has two solutions, so you need to give both.
Sometimes, if the vertex of the parabola is exactly on the x axis, the two roots will be the same. For example:
x^2 -4x + 4 = 0
(x-2)(x-2) = 0
x = 2
x = 2
oh, okay, thank you!
algebra - how would i work out the following problems solve each formula in ...
Pre-Algebra - Please help to solve to find x,y 1. y=7x-3 2. 4x+2y=8 Take the ...
physics Classical Mechanics - Hi, Greco. I am using the following formula to ...
ALGEBRA - I have two problems that I am not sure about how to work out. 1. The ...
Algebra - I have two problems that I am not sure about how to work out. 1. The ...
Algebra - The formula T=2π√L/480 can be used to find the period (T in...
i need help..algebra/math - solve by using the quadratic formula: x2 plus x ...
Algebra - Solve by using the quadratic formula. 3x^2=11x+4. Look up the formula ...
math 213 - The effect of depreciation can be computed using a formula similar to...
algebra - use substitution to solve the linear system 3x+2y=-5 4x-3y=16 help plz...